2022
DOI: 10.1111/dme.14906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio‐economic deprivation on access to diabetes technology in adults with type 1 diabetes

Abstract: Background With advances in technology, there is an emerging concern that inequalities exist in provision and diabetes outcomes in areas of greater deprivation. We assess the relationship between socio‐economic status and deprivation with access to diabetes technology and their outcomes in adults with type 1 diabetes. Methods Retrospective, observational analysis of adults attending a tertiary centre, comprising three urban hospitals in the UK. Socio‐economic deprivation was assessed by the English Indices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…22 Also, among 1631 adults living with T1DM in three urban hospitals in the United Kingdom, the highest use of diabetes technology (continuous subcutaneous insulin infusion, real-time CGM, or flash glucose monitoring) was among the least deprived quintile (67% of those in the least deprived quintile vs 45% in the most deprived quintile). 23 Within our audit, the proportion of participants accessing online onboarding increased in the lower deprivation groups than those accessing face-to-face onboarding (IMD group 1: 9.4% versus 5.3%; IMD group 2: 15.9% versus 12.1%). Importantly, initiation of technology has a positive impact on glycemic control irrespective of the deprivation quintile.…”
Section: Discussionmentioning
confidence: 62%
“…22 Also, among 1631 adults living with T1DM in three urban hospitals in the United Kingdom, the highest use of diabetes technology (continuous subcutaneous insulin infusion, real-time CGM, or flash glucose monitoring) was among the least deprived quintile (67% of those in the least deprived quintile vs 45% in the most deprived quintile). 23 Within our audit, the proportion of participants accessing online onboarding increased in the lower deprivation groups than those accessing face-to-face onboarding (IMD group 1: 9.4% versus 5.3%; IMD group 2: 15.9% versus 12.1%). Importantly, initiation of technology has a positive impact on glycemic control irrespective of the deprivation quintile.…”
Section: Discussionmentioning
confidence: 62%
“…In a cohort of 1631 adults attending a tertiary centre, 24% were using an insulin pump, 19% were using real‐time continuous glucose monitoring (rtCGM) and 34% were using intermittently scanned continuous glucose monitoring (isCGM). Uptake of technology was 67% in the least deprived quintile and 45% in the most deprived, but there was no association between deprivation and HbA 1c outcomes in those using technology 14 . Data from the National Paediatric Diabetes Audit showed that in children and young people, insulin pump use was 31.7% in the most deprived quintile and 44.3% in the least deprived, with figures for rtCGM 14.0% versus 25.2%.…”
Section: Health Inequalities In Diabetesmentioning
confidence: 92%
“…For those with a diagnosis of type 1 diabetes, people in the most deprived groups are less likely to access structured education. A recent observational analysis of 1631 people with type 1 diabetes attending a UK tertiary centre found that only 23% of those in the most deprived quintile had received structured education, compared with 43% in the least deprived quintile 14 . A Scottish study of 335 people who attended a DAFNE course found that socioeconomic deprivation was associated with a higher baseline HbA 1c and a lower reduction in HbA 1c post course 15 …”
Section: Health Inequalities In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Health inequalities are prevalent, complex and represent a significant barrier to public health. Deprivation is a significant factor for access to type 1 diabetes technologies 1 and for the effectiveness of education interventions 2 while the importance of addressing health inequalities to optimise outcomes for those at greatest risk is critical when developing services to support the delivery of care to people with early‐onset type 2 diabetes 3 . Importantly, while the use of type 1 diabetes technologies is related to deprivation, outcomes are not, suggesting that institutional, infrastructure and individual factors at the healthcare provider level should be addressed to remove inequalities.…”
mentioning
confidence: 99%